2005
DOI: 10.1007/s10464-005-8625-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Social Support and Self-Efficacy Within a Recovery Community

Abstract: This study examined similarities and differences in social support and self-efficacy for abstinence between women and men recovering from substance addiction. The sample consisted of 87 residents of Oxford House (OH) self-run, community-based recovery homes. Analyses revealed similarities between women and men in terms of the composition and utilization of support networks and abstinence self-efficacy. Also, for both sexes, length of residency in OH was significantly related to decreased social support for alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 35 publications
(55 reference statements)
6
67
0
Order By: Relevance
“…The literature suggests that the specific setting of Oxford House is beneficial to various recovery outcomes, such as abstinence self-efficacy, social support, and even in reducing anxiety related symptoms than other forms of after-care (Aase, et al, 2006; Jason, Davis et al, 2007; Davis & Jason, 2005; Jason, Olson et al, 2007; Majer et al, 2002). These effects are most pronounced when residents stay for 6 or more months (Jason, Davis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggests that the specific setting of Oxford House is beneficial to various recovery outcomes, such as abstinence self-efficacy, social support, and even in reducing anxiety related symptoms than other forms of after-care (Aase, et al, 2006; Jason, Davis et al, 2007; Davis & Jason, 2005; Jason, Olson et al, 2007; Majer et al, 2002). These effects are most pronounced when residents stay for 6 or more months (Jason, Davis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Oxford House members are expected to attend Alcoholics Anonymous or Narcotics Anonymous (AA/NA) meetings as no formal treatment is provided in the house. Research has demonstrated favorable outcomes for individuals in Oxford House, such as abstinence from alcohol and drug use (Jason, Davis & Ferrari & Anderson, 2007; Jason, Olson, Ferrari, Majer, Alvarez & Stout, 2007), increased abstinence social support (Majer, Jason, Ferrari, Veneble & Olson, 2002) and self-efficacy to refrain from substance use (Davis & Jason, 2005; Jason et al, 2007). However, the literature demonstrates that the most beneficial outcomes occur after 6 or more months of stay in an Oxford House (Jason et al, 2007).…”
Section: The Impact Of Social Anxiety In Aftercare Settingsmentioning
confidence: 99%
“…Perceived social support reflects people's opinions on the provided support and the size of the social network (7). Davos and Jason showed that abstinence from drug abuse was positively associated with perceived social support (8). Another study indicated that social support provided by peers and adults in religious communities could prevent adolescents from engaging in high-risk behaviors (9).…”
Section: Introductionmentioning
confidence: 99%
“…Davis and Jason (2005) explored sex differences in social support and self-efficacy among Oxford Houses’ residents. They found for both men and women, more time as a resident in an Oxford House was related to more self-efficacy for not using alcohol and drugs as well as less social support for use of alcohol or drugs.…”
Section: Introductionmentioning
confidence: 99%
“…They found for both men and women, more time as a resident in an Oxford House was related to more self-efficacy for not using alcohol and drugs as well as less social support for use of alcohol or drugs. Furthermore, women's social networks that had less support for alcohol and drug use had a significant impact on their abstinence self-efficacy (Davis & Jason, 2005). …”
Section: Introductionmentioning
confidence: 99%